Effects of Stream Thermal Variability on Macroinvertebrate Community: Emphasis on Native Versus Non-Native Gammarid Species - Pander, Joachim; Habersetzer, Luis; Casas-Mulet, Roser; Geist, Juergen (Frontiers in Environmental Science, 2022)
An increase in river water temperatures is being detected worldwide, with some predictions of an up to 4 °C rise by 2050. Such stream temperature increase is likely to affect aquatic communities, with predicted declines and range shifts of cold stenothermic species and a facilitated dispersal and population development in temperature-tolerant species, including invasive ones. This study analyzed how thermal changes affect macroinvertebrate community compositions in three differentiated thermal regions within a single stream system. In each thermal region, we used standard surber sampling in combination with in-stream cross-exposure experiments, comparing the thermal response native vs. non-native gammarids (Gammarus roeselii and Dikerogammarus villosus). Macroinvertebrate species composition was highly dependent on temperature, with indigenous gammarids preferring colder sites and invasive ones such as D. villosus being dominant at higher temperatures. Species composition was also strongly affected by season, substratum and the presence of macrophytes. In light of climate change, consideration of shifts in community composition highly driven by temperature needs to become integrated with biological response patterns related to morphological and flow degradation, chemical pollution and fine sediment. Such an approach is crucial for the effective conservation and restoration of native biodiversity and for a realistic prediction of the ability to reach policy targets for aquatic ecosystems.